Dampak Program Kampus Mengajar Bagi Peningkatan Soft Skill (Kemampuan Interpersonal) Dan Hard Skill (Kemampuan Intelektual) Mahasiswa Program Studi Pendidikan Ekonomi Universitas Bhinneka PGRI - Nailariza Umami; Fitria Ramdhani (Jurusan Ekonomi Pembangunan Fakultas Ekonomi Universitas Negeri Malang, 2022)
This study aims to determine whether the teaching campus program has a positive effect on students' hard skills and whether it has a positive impact on the soft skills of students of students of the PGRI economic education study program at Bhinneka University. A sample of 21 students enrolled in the campus teaching program and the economic education study program was used. for this descriptive study. With four soft skill indicators, this instrument is designed to assess student progress in soft and hard skills through campus teaching programs: 1) communication capacity, 2) problem solving capacity, 3) creativity, and 4) conflict resolution capacity. Meanwhile, this study discusses hard skill indicators such as empathy, social skills, use of technology, writing. skills, and research and writing skills. The findings show an increase in students' soft skills, with the highest indicator, their communication skills increasing by 90%. The most important indicators, namely improvement in writing and research, showed a 98% increase in student skills.DOI: https://dx.doi.org/10.17977/UM014v15i22022p94